An uncommon case showing three different pathologies on (99m)technetium-methylene diphosphonate bone scintigraphy - Chakraborty, Partha Sarathi (Indian J Nucl Med, 2015)
(99m)Technetium-methylene diphosphonate bone scintigraphy (BS) has an important role in evaluating skeletal pathology, especially its extent. Incidental extra-osseous uptake may sometimes be seen in soft-tissue pathologies. We present a 64-year-old female with skull base osteomyelitis referred for BS which revealed involvement of the skull base on the left side, uptake was also noted in bilateral lungs secondary to hypercalcemia of renal failure and in the D12-L1 vertebrae as the patient had a history of Pott's spine. This is perhaps a unique case showing three findings each of a different etiology in the same scan.